General legal characteristics of mediation - Yesayan, Vardush (Bulletin of Yerevan University C: Jurisprudence, 2025)
Improving the effectiveness of the mechanism for ensuring human rights and freedoms cannot be achieved solely through the application of imperative methods of legal regulation. Therefore, the importance of so-called “self-regulation” mechanisms is significantly increasing today. Consequently, in order to enhance the effectiveness of the protection of citizens' rights, it is necessary to ensure that the form of dispute resolution corresponds to the nature of the dispute (“Fitting the forum to the fuss”).Alternative dispute resolution involves a process in which a neutral third party is engaged to assist in the resolution of legal disputes through procedures such as mediation, arbitration, and others. One of the methods of alternative dispute resolution is mediation, which is actively used in many countries with developed legal systems. The parties are free to resort to mediation, where a neutral party mediator assists them in reaching a resolution.
Keywords: alternative dispute resolution; protection of rights; alternative dispute resolution procedures; mediation process (mediation); mediator; neutral and impartial; civil disputes